MIGHTEE-H i: the H i size–mass relation over the last billion years. Issue 2 (14th March 2022) - Rajohnson, Sambatriniaina H A; Frank, Bradley S; Ponomareva, Anastasia A; Maddox, Natasha; Kraan-Korteweg, Renée C; Jarvis, Matt J; Adams, Elizabeth A K; Oosterloo, Tom; Baes, Maarten; Spekkens, Kristine; Adams, Nathan J; Glowacki, Marcin; et al.
ABSTRACT: We present the observed H i size–mass relation of 204 galaxies from the MIGHTEE Survey Early Science data. The high sensitivity of MeerKAT allows us to detect galaxies spanning more than 4 orders of magnitude in H i mass, ranging from dwarf galaxies to massive spirals, and including all morphological types. This is the first time the relation has been explored on a blind homogeneous data set that extends over a previously unexplored redshift range of 0 < z < 0.084, i.e. a period of around one billion years in cosmic time. The sample follows the same tight logarithmic relation derived from previous work, between the diameter (D_H I ) and the mass (M_H I ) of H i discs. We measure a slope of 0.501 ± 0.008, an intercept of -3.252^+0.073_-0.074, and an observed scatter of 0.057 dex. For the first time, we quantify the intrinsic scatter of 0.054 ± 0.003 dex ( 10 per cent ), which provides a constraint for cosmological simulations of galaxy formation and evolution. We derive the relation as a function of galaxy type and find that their intrinsic scatters and slopes are consistent within the errors. We also calculate the D_H I \!-\! M_H I relation for two redshift bins and do not find any evidence for evolution with redshift. These results suggest that over a period of one billion years in look-back time, galaxy discs have not undergone significant evolution in their gas distribution and mean surface mass density, indicating a lack of dependence on both morphological type and redshift.